Inhibiting the inverse Hall-Petch behavior in CoCuFeNiPd high-entropy alloys with short-range ordering and grain boundary segregation - Ji, Weiming (2022)
The mechanical implications of short-range ordering (SRO) and grain boundary (GB) segregation in the inverse Hall-Petch behavior of nanocrystalline CoCuFeNiPd high-entropy alloys (HEAs) were studied using hybrid Monte Carlo (MC)/Molecular Dynamics (MD) simulations. Results show that the presences of SRO and GB segregation inhibit the grain size softening (inverse Hall-Petch relation), leading to grain-size independence of the high flow stress. We find that the dislocation nucleation at triple junctions is suppressed by the SRO due to the increased stacking fault energy, which attenuates the dislocation activities. Furthermore, the strain localization at GBs is intensified by the GB segregation due to the increased GB energy, which facilitates the GB activities and glass-like deformation. The GB-governed plasticity associated with glass-like deformation leads to suppression of the inverse Hall-Petch effect. These findings may provide useful strategies for the design of high-performance HEAs by tuning the GB composition and SRO structure.